Circulating human CD4 and CD8 T cells do not have large intracellular pools of CCR5 - Pilch-Cooper, Heather A. (American Society of Hematology, 2011)
CC Chemokine Receptor 5 (CCR5) is an important mediator of chemotaxis and the primary coreceptor for HIV-1. A recent report by other researchers suggested that primary T cells harbor pools of intracellular CCR5. With the use of a series of complementary techniques to measure CCR5 expression (antibody labeling, Western blot, quantitative reverse transcription polymerase chain reaction), we established that intracellular pools of CCR5 do not exist and that the results obtained by the other researchers were false-positives that arose because of the generation of irrelevant binding sites for anti-CCR5 antibodies during fixation and permeabilization of cells.